The operational units approach for fisheries management in the mediterranean sea - Accadia, P.; Franquesa, R. (Roma (Italia), 2006)
Sumario (En)
Ilus.; 9 ref.
Keywords: PESCA; RECURSOS PESQUEROS; VIGILANCIA; ESTUDIOS DE CASOS PRACTICOS; ORDENACION DE RECURSOS; MAR MEDITERRANEO